The Effect Of Quiz-Based Interactive Media On Civic Education Learning Outcomes In Third Grade - Rolita Dolok Saribu; Janwar Tambunan; Emelda Thesalonika (Jurnal Ilmiah Multidisiplin Nusantara (JIMNU), 2025)
The purpose of this study was to determine the effect of quiziz-based interactive media on Civics learning outcomes in class III of UPTD SD Negeri 124392 Pematangsiantar. This study was quantitative with a one-group pretest-posttest design. The sample of this study was all students of class III of UPTD SD Negeri 124392 Pematangsiantar in the 2025/2026 academic year, totaling 25 people. The research instrument used in this study was a learning outcome test instrument, the data obtained were analyzed using statistical analysis techniques. Data from the initial conditions before the treatment was carried out until after the treatment was carried out showed an increase in student learning outcomes. Before the treatment, the average score was 68 and after the treatment, the average score was 84. It can be concluded that the student learning outcomes before the treatment were given were still not reaching the KKTP, namely 25 students (100%) and after the treatment, student learning outcomes increased, namely 26 students (100%) had scores above the KKTP. Based on the results of the hypothesis test with a significance level of 0.05 and a t table of 2.060, the calculated t is 11.238. Thus, t count > t table 11.238 > 2.060, it can be concluded that there is an influence of Quiziz-based interactive media on Civics learning outcomes in grade III at the UPTD of SD Negeri 124392 Pematangsiantar